PENGARUH PEREGANGAN STATIS DAN DINAMIS TERHADAP PERUBAHAN INTENSITAS NYERI SENDI LUTUT PADA LANSIA DENGAN OSTEOARTHRITIS - Pradnya Paramitha Pemaron (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Osteoarthritis is the most common rheumatic disease of the elderly. Osteoarthritis characterized by mild inflammation in the synovium that can cause symptoms such as joint pain. Supporting non-pharmacological therapy that can relieve joint joint pain, one of which that can be used in the pain management is physical therapy including static and dynamic stretching. Static and dynamic stretching helps muscle contraction-relaxation more quick and efficiently, increase joint flexibility to minimize the friction that occurs due to the increased stiffness of the joints and stimulates the release of endorphin hormones that can reduce the sensation of pain. This research aims to determine the effect of giving static and dynamic stretching for Joint Pain Intensity Alteration In Elderly with Knee Osteoarthritis. This research were quasi experimental design with nonequivalent control group design. Samples were 20 elderly with Knee Osteoarthritis recruited using purposive sampling, divided into experimental and control group. The subject in the stretching group was given 15 minutes of stretching exercises three times a week for a month whereas the subjects of control group only observed. Pain intensity pre-test and post-test in both groups recorded on the observation sheet. The subject in the stretching group showed a decrease in the average value of 1,01, whereas the subjects of control group showed a increase in the average value of 0,30. Independent sample t test results showed p value sig. (2-tailed) = 0.00 (p < 0.05) which means that there are significant of dynamic and static stretching to changes in the intensity of joint pain in older adults with knee osteoarthritis.